SilentSecrecy: Hiding in Image and Audio Using Spread Spectrum Technique with an Image Stenalysis Plug-In - Moo, Chui Lih; Beh Mei Yin, Delina; Azmanuddin, Nurul Sharaz (Journal of Computing Technologies and Creative Content, 2016)
This paper presents a proposed scheme which employs a steganography technique to hide and retrieve data or file along with steganalysis technique to analyse suspicious image file. Due to the growth of technology, people tend to keep information electronically. Private information can be obtained by unauthorised use without knowing. With the usage of both steganography and encryption method, the unauthorised user might have difficulty on getting user private information. On the other hand, steganalysis is an ill-posed problem. The original host data is unknown, the rate of hiding (if data is hidden) is not known and the number of steganography scheme is large. In this research, it will clarify what steganography is, the definition, the technique used in implementing steganography as well as steganalysis. This study focuses on the Spread Spectrum technique in hiding data or file in a media file (MP3 and JPEG) and statistical steganalysis technique that is Chi-Square attack. The proposed scheme is then analysed and evaluated the payload size, stego image resolution and the occurrence of hidden data in an image file. The significance of the proposed scheme is the user can embed and retrieve secret data from media file, while Chi-Square attack able to analyse the hidden message in an image.